Exposure risk management: Personal protective equipment and the risk of accidents occurring during aerosol generating procedures applied to COVID-19 patients. - Ștefan Andrei Neştian; Silviu-Mihail Tiţă; Elena-Sabina Turnea; Oana Stanciu; Vladimir Poroch (PLoS ONE, 2023)
Background COVID-19 is considered to be very contagious as it can be spread through multiple ways. Therefore, exposure risk of healthcare workers (HCWs) treating COVID-19 patients is a highly salient topic in exposure risk management. From a managerial perspective, wearing personal protective equipment and the risk of accidents occurring during aerosol generating procedures applied to COVID-19 patients are two interconnected issues encountered in all COVID-19 hospitals. Objective The study was conducted to understand the realistic impact of exposure risk management on HCWs exposed to risks of SARS-CoV-2 virus infection in a healthcare unit. In particular, this study discusses the role of personal protective equipment (PPEs) used in aerosol generating procedures (AGPs) to protect HCWs, and the related risk of accidents occurring when performing AGPs. Methodology This is a cross-sectional single-hospital study conducted at the "Sf. Ioan cel Nou" Hospital in Suceava, Romania, that had to ensure safety of healthcare workers (HCWs) getting in contact with COVID-19 cases. Data used in the study were collected between 10.12.2020-19.03.2021 by means of a questionnaire that collected information on risk assessment and healthcare workers' exposure management, and which was translated and adapted from the World Health Organization (WHO) and applied to respondents online. For this purpose, ethical approval was obtained, doctors and nurses from all hospital departments being invited to complete the questionnaire. Data processing, as well as descriptive, correlation and regression analyses have been done by using the 21.0 version of the Statistical Package for Social Sciences software. Results Most of the 312 HCWs reported having always used disposable gloves (98.13%), medical masks N95 (or equivalent) (92.86%), visors or googles (91.19%), disposable coverall (91.25%) and footwear protection (95.00%) during AGPs. The waterproof apron had always been worn only by 40% of the respondents, and almost 30% of staff had not used it at all during AGPs. Over the last three months, the period when the questionnaire was completed, 28 accidents were reported while performing AGPs: 11 accidents with splashing of biological fluids/ respiratory secretions in the eyes, 11 with splashing of biological fluids/ respiratory secretions on the non-idemn skin, 3 with splashing of biological fluids/ respiratory secretions in the oral/ nasal mucosa and 3 with puncture/ sting with any material contaminated with biological fluids/ respiratory secretions. Also, 84.29% of respondents declared having changed their routine, at least, moderately due to COVID-19. Conclusion An effective risk exposure management is based on wearing protective equipment. The only protection offered by the disposable coverall, as it results from our analysis, is related to splashing of biological fluids/ respiratory secretions on the non-idemn skin. In addition, the results show that the number of accidents should decrease due to the fact that disposable gloves and footwear protection are used while performing AGPs on patients with COVID-19 and hand hygiene is practised before and after touching a patient with COVID-19 (regardless of glove wearing).